A model to facilitate transformative learning in nursing education - Tebogo A. Tsimane; Charlene Downing (Elsevier, 2020)
Objective: Transformative learning is a learner-centered process of learning. Learners are actively engaged through critical reflection and discourse to question assumptions and expectations. The purpose of this article is to describe a model to facilitate transformative learning in nursing education. Methods: A qualitative, exploratory, descriptive and contextual design for theory generation was selected in this study to describe a model to facilitate transformative learning in nursing education. Concept analysis of transformative learning was done in the first stage of the main study using Walker and Avant's eight step approach to clarify the conceptual identification and meaning. The results of concept analysis guided data collection in the second stage. Eleven individual agenda semi-structured interviews were conducted with nurse educators to explore and describe their perceptions regarding how transformative learning can be facilitated in nursing education. Matrix building approach was used to analyse the collected data. The third stage constituted the conceptualisation of findings from the second stage using relevant literature within the elements of practice theory. The fourth stage focused on the description and evaluation of a model to facilitate transformative learning in nursing education. Findings: Four themes and nine sub-themes emerged and were conceptualised within the six elements of practice theory namely the context, agent, recipient, dynamic, process and procedure and outcome. Conclusion: The relation statements provided the basis for model description. Reliable method was used to describe and evaluate the model. The refinement of the model by experts in model development and qualitative research was made.